Infeksi nosokomial saluran kemih paska kateterisasi urin pada anak - Lorinda R.P. Harahap; Rafita Ramayati; Rusdidjas dr; Oke Rina Ramayani; Rosmayanti Siregar; Beatrix Siregar (Fakultas Kedokteran USU, 2014)
Urinary catheters are often used in hospitalized patients and this could be potentially a infection. It is estimated that approximately 80% hospital-acquired urinary tract infection (UTI) associated with catheter use. aim of the study is to determine relationship between use of urinary catheter with nosocomial urinary tract infection in children.Keywords : urinary catheter; nosocomial urinary tract infection; children